(untitled) (AGROINNOVATSIYА, 2024)
Studying and knowing the biological properties of primary materials, the most important economic characteristics of oriental dates in the study of varieties, comparing them with existing varieties, testing them in different climatic conditions, bioecological characteristics of the studied varieties of oriental dates growth and development, morphological indicators, ability to fully adapt to the conditions of introduction, indicate the possibility of growing this plant in the southern lands of Uzbekistan.